Quality of life and its contributors among patients with homozygous familial hypercholesterolemia in China - Tang, Mi; Ye, Ziping; Zhang, Xueyan; He, Jiangjiang; Kang, Qi; Tang, Zhenqing; Wang, Luya; Yang, Ya; Yang, Yan; Hu, Shanlian (Frontiers in Public Health, 2025)
BackgroundChina is one of the countries with the largest number of patients with homozygous familial hypercholesterolemia (HoFH) in the world. Improving the quality of life and health outcomes for HoFH patients in China is of great importance. Therefore, the aim of this study is to assess the quality of life of HoFH patients in China and to investigate the factors that influence quality of life.MethodsData were obtained from a national epidemiological survey of HoFH patients conducted by Beijing Anzhen Hospital, affiliated with Capital Medical University, during 2017–2019. The questionnaire included patient demographic information, disease information, family economic status and health-related quality of life. Quality of life was assessed using the EuroQol five-dimension three-level (EQ-5D-3L) questionnaire. Data processing and statistic tests are performed using Python libraries.ResultsThis investigation incorporated a sample size of 53 patients diagnosed with HoFH, with an average age of 27.92 years. It was observed that 45.28% of these patients' families were subjected to catastrophic health expenditure. The mean and median health utility scores were calculated to be 0.849 and 0.875, respectively, a figure that is significantly lower when compared to the scores of the general population. Furthermore, it was noted that 52.83% of the patients exhibited some level of difficulty or extreme difficulty in at least one dimension of the EQ-5D-3L. Significant Factors negatively affecting the quality of life of HoFH patients include the presence of atherosclerotic cardiovascular disease (ASCVD), hospitalisation in the past year, taking multiple medications, higher than average healthcare expenditure per capita, catastrophic healthcare expenditure and debt due to HoFH. After application of Benjamini-Hochberg method to minimize type 1 error, the occurrence of ASCVD and debt due to HoFH are likely to exert the most significant influence. Substantial relevance of the two factors are also evidenced by large effect sizes and adequate statistical power.ConclusionsChinese patients with HoFH showed lower quality of life than the general population. Policy makers should consider the policy that improves early diagnosis, employment prospects, and the availability of HoFH-related interventions and provision of financial assistance for patients suffering from HoFH.